2014
DOI: 10.1186/1475-2875-13-502
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of malaria and acceptance of rapid diagnostic tests and related treatment practises among community members and health care providers in Greater Garissa, North Eastern Province, Kenya

Abstract: BackgroundConventional diagnosis of malaria has relied upon either clinical diagnosis or microscopic examination of peripheral blood smears. These methods, if not carried out exactly, easily result in the over- or under-diagnosis of malaria. The reliability and accuracy of malaria RDTs, even in extremely challenging health care settings, have made them a staple in malaria control programmes. Using the setting of a pilot introduction of malaria RDTs in Greater Garissa, North Eastern Province, Kenya, this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…A high care taker acceptability was observed, and this may be attributed to the fact that the community members are the ones who choose a person to be trained as a CHW. Another study conducted in Kenya found that CHWs had good knowledge related to malaria transmission, prevention,and management including diagnosis and treatment (Diggle et al, 2014)if not carried out exactly, easily result in the over-or under-diagnosis of malaria. The reliability and accuracy of malaria RDTs, even in extremely challenging health care settings, have made them a staple in malaria control programmes.…”
Section: Introductionmentioning
confidence: 99%
“…A high care taker acceptability was observed, and this may be attributed to the fact that the community members are the ones who choose a person to be trained as a CHW. Another study conducted in Kenya found that CHWs had good knowledge related to malaria transmission, prevention,and management including diagnosis and treatment (Diggle et al, 2014)if not carried out exactly, easily result in the over-or under-diagnosis of malaria. The reliability and accuracy of malaria RDTs, even in extremely challenging health care settings, have made them a staple in malaria control programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst it is therefore not possible to draw direct conclusions from these data about the causes of ACT non-prescription, a number of possible explanatory factors were suggested by Burchett et al [19], including motivation to perform well in a study context, stability of ACT supplies, and local preferences for different types of antimalarials. More broadly, other previous work has identified some factors that are associated with non-adherence to test results and/ or treatment guidelines, including distrust in the test or test result [36][37][38][39], patient demands or preferences for a particular medication [19,[40][41][42][43], perceptions of low drug efficacy [41], staff workload [44], financial incentives [42], level of health care worker [41,45,46], affordability and accessibility of non-recommended therapies [47,48], and rationing of medications [19,49]. Stock-outs of weightspecific drug packs can also lead to inappropriate prescription of medications [45,50], whilst lack of knowledge on how to prescribe second-line drugs can lead to not prescribing them at all [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical and laboratory staff did feel that POCT may allow the women to become more involved in their healthcare and therefore more likely to comply with healthcare recommendations. Studies reveal complex relationships between active patient participation, patient adherence, intervention implementation and expected health outcomes in malaria and anaemia management (9,20,21). Patient-centred approaches can have an impact on a healthcare practitioners' approach to care and this could be considered in the development of any training package for the implementation of POCT.…”
Section: Stakeholder Relationshipsmentioning
confidence: 99%